Emotional salary and agile management: Organizational well-being as an outcome - Pérez, Enmanuel (REVISTA CIENTIFICA GLOBAL NEGOTIUM, 2025)
Digital transformation has driven the need for new human talent management models that strengthen employee well-being. This study aimed to explore the relationship between emotional salary and agile management and their impact on organizational well-being. Using a mixed paradigm, the quantitative phase addressed employees in the Latin American technology sector. In the qualitative phase, in-depth interviews were conducted with HR leaders and managers. The quantitative results revealed a positive and significant correlation between agile management and emotional salary, as well as between emotional salary and organizational culture. The qualitative findings complemented these results, highlighting that practices such as continuous feedback, autonomy, and collaboration are key elements of agile management that influence emotional salary. Furthermore, the study found evidence that emotional salary acts as a mediator between agile management and employee well-being. It is concluded that the implementation of agile management practices is an effective strategy to strengthen emotional salary and, consequently, promote a healthy organizational culture. The implications of these findings for talent management are discussed, as well as the limitations of the study and future lines of research.
Keywords: Agile management; Emotional salary; Organizational well-being; digital transformation